Dental implants from laser fusion of titanium microparticles: from research to clinical applications - Mangano, Carlo; Shibli, Jamil Awad; Mangano, Francesco; Sammons, Rachel; Macchi, Aldo (Journal of Osseointegration, 2009)
Dental implants currently available on the market are conventionally produced by machining titanium rods, with subsequent application of surface treatments or coatings, with the aim to accelerate the bone healing process. The progress in the field of rapid prototyping technology makes it possible to modulate the elastic properties of the implants to those of surrounding bone. The direct laser fabrication (DLF) allows solids with complex geometry to be produced by focusing metal powder microparticles in a laser beam, according with a computer three-dimensional (3D) model. For dental implants, the fabrication process involves the fusion, through a computer guided laser beam, of titanium microparticles, in order to realise, layer by layer (each one with a thickness of 20 Ìm) the desired object. Our Research Group, first in the world, has developed a method to produce dental implants using a laser fusion of titanium microparticles. With this method it is possible to create, regulating the settings of the different layers, implants with graduated and controlled porosity, incorporating a gradient of porosity, from the inner core to the outer surface. On the one hand, this kind of modulation can allow a better load adaptation and distribution; on the other hand, the new porous surface can promote the bone healing process. The new implants obtained from the fusion of titanium microparticles show a surface with a repetitive sequence of concavities, which are directly connected to the underlying porous spaces. This kind of geometry, rich in interconnected pores, has demonstrated in previous works to induce a good biological response in vitro. The aim of the present study was to test the biological behaviour of the new implants obtained from the fusion of titanium microparticles (TixOs, Leader-Novaxa, Milan, Italy) in vivo, in human type IV bone, after an unloaded healing period of two months.